Corporate plagiarism during remote work – a concern? - Khan, Zeenath Reza; Arvikar, Atharv; Venugopal, Swathi; Hemnani, Priyanka (Canadian Perspectives on Academic Integrity, 2021)
Plagiarism is a type of academic misconduct that has plagued the education sector for years. It may be one of the most common forms of academic misconducts that is identified in schools (K-12) and higher education sector. Plagiarism is when someone uses someone else’ intellectual property and passes it off as own work without any acknowledgement or attribution. While the topic is well documented and discussed in the academic world, very little is known about how it plays out in the corporate world (Reyman, 2008), except that some studies have shown that students who have a tendency to engage in academic misconduct in academia also demonstrate propensity for unethical practices in the workplace (Khan, al-Qaimari & Samuel, 2007; Daniel et al., 2009). Preliminary discussions during a virtual summit in a Middle Eastern country involving participants from corporate sectors across the region revealed concerns over employees copying and pasting text, code, images and other property when working on company reports or developing digital products. Particular concern arose over “outsourcing” of certain business functions such as “marketing” and “digital content creation”. Some participants shared how they were pressured to create content for clients within unrealistic timeframes and expected to either copy from the web or simply reuse content previous created for other clients. Concerns were focused on corporate sector, but also included administrative staff at educational institutions such as faculty coordinators, marketing and digital content staff, library and registrars’ staff, student services staff, and so on. Majority of concerns discussed revolved around lack of prior knowledge of concepts such as plagiarism among employees during their education career, or copyright and intellectual property infringements; while for educational institutions, the concern was over lack of focus on need to raise awareness among non-faculty staff, beyond courses and subject content. This presentation proposes to look at plagiarism that takes place in the corporate world and how that has become a new concern in the era of remote work due to the COVID19 pandemic, irrespective of the sector the company is in and how academic world can support corporate sector and better prepare future professionals.